Effect of Social Economics to Reading Interest Learning Programs of Equal Education Programs - Irfan Ardiansyah; Bayu Pradikto (Pancaran Pendidikan, 2018)
According to the survey of the United Nations Education, Scien tific and Cultural Organization (UNESCO) in 2012, low interest in reading in Indonesia, evidenced by an index reading of Indonesian society only 0,001 (one thousand inhabitants, there is only one person who still has a high interest). While the average reading index in developed countries ranges from 0.45 to 0.62. For the ASEAN region itself, Indonesia ranks third bottom or above Cambodia and Laos (www.republika.co.id). Other data, according to the study results "Most littered Nation in the World" by the Central Connectticut State University (March 2016), Indonesia was ranked 60 out of 61 countries a matter of interest in reading. And based infrastructure, Indonesia at number 34 over Germany, Portugal, New Zealand and South Korea